2021
DOI: 10.1039/d1ra01640g
|View full text |Cite
|
Sign up to set email alerts
|

Peroxymonosulfate activation by tea residue biochar loaded with Fe3O4 for the degradation of tetracycline hydrochloride: performance and reaction mechanism

Abstract: The prepared tea residue biochar loaded with Fe3O4 has high-efficiency and environmental potential for activating peroxymonosulfate to degrade tetracycline hydrochloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…[1][2][3] Recently, biochar has been found to be an attractive catalyst for advanced oxidation of pollutants. [4][5][6] Specically, biochar can activate H 2 O 2 , 7-10 and persulfates [11][12][13] to produce reactive oxygen species (ROS) such as the hydroxyl radical (cOH), sulfate radical (SO 4 c À ) and singlet oxygen ( 1 O 2 ), which are powerful oxidants (e.g. E q (cOH/H 2 O) ¼ 2.73 V) capable of mineralization of various organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, biochar has been found to be an attractive catalyst for advanced oxidation of pollutants. [4][5][6] Specically, biochar can activate H 2 O 2 , 7-10 and persulfates [11][12][13] to produce reactive oxygen species (ROS) such as the hydroxyl radical (cOH), sulfate radical (SO 4 c À ) and singlet oxygen ( 1 O 2 ), which are powerful oxidants (e.g. E q (cOH/H 2 O) ¼ 2.73 V) capable of mineralization of various organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…As evident from the degradation pathway, the intermediate products with m/z 172, 136, 127, 117, and 86 are formed through ring opening, cleavage of the ring with hydroxylation and deprotonation. 73,79 The molecules with less m/z values may be subsequently degraded into less hazardous products such as carbon dioxide and water.…”
Section: Lcms Analysismentioning
confidence: 99%
“…The magnetic property of CuFe 2 O 4 catalyst was measured by VSM at room temperature and obtained magnetization hysteresis loop was shown in Figure 6. Obviously, the magnetization curve with closed S-shaped pass through the coordinate origin, which indicated that the catalyst has paramagnetism and reversible magnetization state, and is a soft magnetic material (Wang et al 2021). It could be seen from the figure that the magnetization curve of CuFe 2 O 4 catalyst was close to the saturation magnetization region when the magnetic field was applied in the forward and reverse directions.…”
Section: Vsmmentioning
confidence: 99%
“…Under the condition of constant catalyst dosage and PMS concentration, a certain amount of reactive species was provided. It indicated that effective reaction probability decreased with the increasing initial concentration of LEV(Wang et al 2021). Notably, with the progress of reaction time, the LEV degradation efficiency at different LEV initial concentration inclined to the same.…”
mentioning
confidence: 95%